Public Knowledge Regarding Coronavirus Disease 19 - Tegar Wahyu Priambodo (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Covid-19 outbreak occurred in December 2019 in Wuhan, China, and was named Coronavirus Disease 2019. This Covid-19 phenomenon is a new disease. As time goes on and research continues to be carried out, there are lots of changing facts, that will imply the level of public knowledge about Covid-19 and the public’s attitude in dealing with it as its part of mitigating this virus. Thus, it is necessary to research the level of public knowledge regarding Covid-19. The method used in this research is to analyze from various reading sources and references taken are from the national journal. This study took 4 journals as references from the four journals, all of which showed that public knowledge about the Covid-19 phenomenon was good. From the journals that were used as references, information was obtained about the level of public knowledge about the Covid-19 phenomenon in various regions in Indonesia, but further research must be carried out to determine the level of public knowledge about Covid-19